The relationship between discipline and academic performance : towards building sustainable teaching and learning behaviours in schools. - Foncha, John W.; Ngoqo, V. M.; Mafumo, T. N.; Maruma, M. W. (Gender and Behaviour, 2017)
The purpose of this paper is to show that quality teaching and learning are the bed rock of discipline and academic performance. The main aim is to show how the escalation of indiscipline has effect on the academic performance of the learners. Indiscipline has become strife in schools and which has plunged our learners to a level where they are uncontrollable. To this effect, something needs to be done to build a good citizenry. The study is interpretive in nature within a qualitative design based on the case study of one urban school. The population included the teachers and the learners and the tools for data collection included observation, interviews and naturally occurring data. The study revealed that quality teaching and learning in schools lead to discipline and academic performance. It concluded that discipline can only be sustained if it is based on the rules drafted and owned by the community.
Journal article published in the journal of Gender and Behaviour
Keywords: Discipline; Learning behavious; School; Academic performance; Effective teaching; Academic achievement; School discipline -- South Africa; Teacher effectiveness